Fine mapping of the dyskeratosis congenita locus in Xq28. Issue 12 (December 1996) - Knight, S W; Vulliamy, T; Forni, G L; Oscier, D; Mason, P J; Dokal, I
Abstract : Dyskeratosis congenita (DC) is characterised by reticulate skin pigmentation, mucosal leucoplakia, and nail dystrophy. Bone marrow failure occurs in 50% of patients and is the principal cause of early mortality. In the majority of families the pattern of inheritance of DC is compatible with an X linked recessive trait. The locus for the X linked recessive form of DC has been linked to Xq28. We have now extended our earlier studies by investigating five families with additional Xq28 polymorphic markers; analysis of recombination events in these families has located the DC1 locus between GABRA3 and DXS1108, an interval of approximately 4 Mb.